HUBUNGAN SERVICE QUALITY DAN CUSTOMER TRUST DENGAN LOYALITAS PENGUNJUNG WISATA JUNGLELAND ADVENTURE THEME PARK SENTUL BOGOR - Mujito Mujito; Hari Muharram; Jan Horas V. Purba (MAGMA : JURNAL MAGISTER MANAJEMEN, 2021)
The purpose of this study was to determine and analyze the relationship between service quality and customer trust with the loyalty of visitors to Jungleland Sentul Bogor. The study was conducted at the Sentral Jungleland Adventure Park, Bogor. In this research, the writer uses quantitative methods. The population of this study is all consumers / visitors of Sentul Jungleland Tourism Object Bogor. The sampling method used was purposive sampling. The sample in this study was chosen based on the visitor's understanding of the research object. In this study the number of samples taken was 10 x the number of subvariables (13) so in this study the sample was 130 samples. Data analysis uses multiple linear regression with the help of the SPSS program.The results showed there was a positive and significant relationship between service quality variables with consumer loyalty with a correlation coefficient (r) of 0.859, which means very strong. And the contribution of service quality (X1) to consumer loyalty (Y) obtained R Square value (R²) of 0.738, this means that service quality (X1) contributed 73.8% to consumer loyalty (Y). There is a positive and significant relationship between the trust variable and consumer loyalty with a correlation coefficient (r) of 0.717, which means strong. And the contribution of the trust variable (X2) to consumer loyalty (Y) obtained an R Square value of 0.514, this means that the trust variable (X2) formed a contribution of 51.4% to consumer loyalty (Y). There is a positive and significant relationship between service quality and trust variables together with consumer loyalty with a correlation coefficient (r) of 0.922, which means very strong. And the contribution of servive quality (X1) and trust (X2) together to consumer loyalty (Y) obtained Adjusted R Square (R²) value of 0.848, this shows that 84.8% of Jungleland Sentul Bogor consumer loyalty is influenced by service quality and trust while the remaining 15.2%, consumer loyalty Jungleland Sentul Bogor is influenced by other factors which in this study were not discussed. The most dominant variable affecting consumer loyalty Jungleland Sentul Bogor is the service quality variable (X1) with a regression coefficient of 0.481.